An update on periodontal inflammation and bone loss - Zhang, Mingzhu; Liu, Yali; Afzali, Hamideh; Graves, Dana T. (Frontiers in Immunology, 2024)
Periodontal disease is a chronic inflammatory condition that affects the supporting structures of the teeth, including the periodontal ligament and alveolar bone. Periodontal disease is due to an immune response that stimulates gingivitis and periodontitis, and its systemic consequences. This immune response is triggered by bacteria and may be modulated by environmental conditions such as smoking or systemic disease. Recent advances in single cell techniques and in vivo animal studies have provided new insight into the immune response triggered by bacteria that causes periodontitis and gingivitis, and its systemic consequences. Dysbiosis, which constitutes a change in the bacterial composition of the microbiome, is a key factor in the initiation and progression of periodontitis. The host immune response to dysbiosis involves the activation of various cell types, including keratinocytes, stromal cells, neutrophils, monocytes/macrophages, dendritic cells and several lymphocyte subsets, which release proinflammatory cytokines and chemokines. Periodontal disease has been implicated in contributing to the pathogenesis of several systemic conditions, including diabetes, rheumatoid arthritis, cardiovascular disease and Alzheimer's disease. Understanding the complex interplay between the oral microbiome and the host immune response is critical for the development of new therapeutic strategies for the prevention and treatment of periodontitis and its systemic consequences.